2013
DOI: 10.1007/s10126-013-9529-9
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Shrimp Penaeus monodon from WSSV Infection Using Antisense Constructs

Abstract: White spot syndrome caused by white spot syndrome virus (WSSV) is one of the most threatening diseases of shrimp culture industry. Previous studies have successfully demonstrated the use of DNA- and RNA-based vaccines to protect WSSV infection in shrimp. In the present study, we have explored the protective efficacy of antisense constructs directed against WSSV proteins, VP24, and VP28, thymidylate synthase (TS), and ribonucleotide reductase-2 (RR2) under the control of endogenous shrimp histone-3 (H3) or pena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
8
1
1
Order By: Relevance
“…Temporal analysis of vp39 gene expression showed it to be expressed after 12 h of viral infection, and its presence was observed in both virions and the viral envelop (Zhu et al, 2006). While 90% protection by the antisense construct in P. monodon was reported by Ahanger et al (2014) with the challenge dose of 1 × 10 3 WSSV, in our study on L. vannamei, 60% protection at day 9 was registered with a challenge dose of 2 × 10 4 copies. There may be a link between the protections offered versus the WSSV challenge dose.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…Temporal analysis of vp39 gene expression showed it to be expressed after 12 h of viral infection, and its presence was observed in both virions and the viral envelop (Zhu et al, 2006). While 90% protection by the antisense construct in P. monodon was reported by Ahanger et al (2014) with the challenge dose of 1 × 10 3 WSSV, in our study on L. vannamei, 60% protection at day 9 was registered with a challenge dose of 2 × 10 4 copies. There may be a link between the protections offered versus the WSSV challenge dose.…”
Section: Discussioncontrasting
confidence: 74%
“…La Fauce and Owens (2013) used antisense plasmid constructs in live bacterial cells to orally deliver short interfering RNA against the shrimp virus Penaeus merguiensis densovirus, a strain of hepatopancreatic parvovirus, in a cricket model. Later, Ahanger et al (2014) reported the effect of antisense constructs against WSSV infection in P. monodon both in vivo and in vitro. They used antisense RNA constructs against WSSV ORFs (VP24, VP28, thymidylate synthase and ribonucleotide reductase-2) under the control of constitutive host promoters such as histone3 and penaeidin, and found substantial protection from WSSV infection both in haemocyte cell cultures (derived from P. monodon and Scylla serrata) and experimental P. monodon.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Teknologi vaksinasi menggunakan agen virus dsRNA berkembang sangat pesat terutama dibidang medis, pertanian, dan akuakultur (Jin et al, 2010;Lichner et al, 2003;Rowley & Pope, 2012). Di bidang akuakultur, teknologi ini banyak dikembangkan untuk menanggulangi penyakit yang disebabkan oleh virus pada udang (Mejía-Ruíz et al, 2011;Ahanger et al, 2014). Beberapa penelitian vaksinasi udang menggunakan agen WSSV sebagai sumber vaksin telah menunjukkan kemajuan dan memperoleh hasil yang menggembirakan (Huang et al, 2014;Kumar et al, 2015;Puneeth et al, 2017).…”
Section: Pendahuluanunclassified